A unique cytoskeleton associated with crawling in the amoeboid sperm of the nematode, Ascaris suum (The Rockefeller University Press, 1989)
Nematode sperm extend pseudopods and pull themselves over substrates. They lack an axoneme or the actin and myosins of other types of motile cells, but their pseudopods contain abundant major sperm protein (MSP), a family of 14-kD polypeptides found exclusively in male gametes. Using high voltage electron microscopy, a unique cytoskeleton was discovered in the pseudopod of in vitro-activated, crawling sperm of the pig intestinal nematode Ascaris suum. It consists of 5-10-nm fuzzy fibers organized into 150-250-nm-thick fiber complexes, which connect to each of the moving pseudopodial membrane projections, villipodia, which in turn make contact with the substrate. Individual fibers in a complex splay out radially from its axis in all directions. The centripetal ends intercalate with fibers from other complexes or terminate in a thickened layer just beneath the pseudopod membrane. Monoclonal antibodies directed against MSP heavily label the fiber complexes as well as individual pseudopodial filaments throughout their length. This represents the first evidence that MSP may be the major filament protein in the Ascaris sperm cytoskeleton. The large fiber complexes can be seen clearly in the pseudopods of live, crawling sperm by computer-enhanced video, differential-interference contrast microscopy, forming with the villipodia at the leading edge of the sperm pseudopod. Even before the pseudopod attaches, the entire cytoskeleton and villipodia move continuously rearwards in unison toward the cell body. During crawling, complexes and villipodia in the pseudopod recede at the same speed as the spermatozoon moves forward, both disappearing at the pseudopod-cell body junction. Sections at this region of high membrane turnover reveal a band of densely packed smooth vesicles with round and tubular profiles, some of which are associated with the pseudopod plasma membrane. The exceptional anatomy, biochemistry, and phenomenology of Ascaris sperm locomotion permit direct study of the involvement of the cytoskeleton in amoeboid motility.